2023
DOI: 10.1186/s12891-023-06640-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatty infiltration of the multifidus muscle independently increases osteoporotic vertebral compression fracture risk

Abstract: Background Vertebral compression fractures decrease daily life activities and increase economic and social burdens. Aging decreases bone mineral density (BMD), which increases the incidence of osteoporotic vertebral compression fractures (OVCFs). However, factors other than BMD can affect OVCFs. Sarcopenia has been a noticeable factor in the aging health problem. Sarcopenia, which involves a decrease in the quality of the back muscles, influences OVCFs. Therefore, this study aimed to evaluate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…Our analysis revealed that multifidus SMI is an independent protective factor against NVCF after PVP/PKP. Consistent with Lee et al ( 31 ), who found no difference in average CSA of multifidus between OVCF with osteoporosis, OVCF with bone loss, and the non-OVCF groups. However, multifidus FCSA in the OVCF group was significantly lower than the non-OVCF group.…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis revealed that multifidus SMI is an independent protective factor against NVCF after PVP/PKP. Consistent with Lee et al ( 31 ), who found no difference in average CSA of multifidus between OVCF with osteoporosis, OVCF with bone loss, and the non-OVCF groups. However, multifidus FCSA in the OVCF group was significantly lower than the non-OVCF group.…”
Section: Discussionsupporting
confidence: 90%
“…Lee et al ( 64 ) showed a significant association between multifidus muscle percentage of muscle fibre and OVF al L4/L5–L5/S1, but not with multifidus muscle CSA which appeared to be higher in the fracture group when compared to the control group. According to this study group the fatty infiltration of the paraspinal muscle, rather than the muscle CSA, significantly affect the risk of OVF.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, it is noteworthy that their study solely encompassed female participants, a factor that might have had a bearing on the results. 27 Jeon et al examined 55 consecutive patients with OVF who were treated conservatively in a single spine center. Their study ascertained that fatty degeneration of the paraspinal muscles was a predictor of progressive vertebral collapse.…”
Section: Discussionmentioning
confidence: 99%